Novel Factors Regulating Proliferation, Migration, and Differentiation of Fibroblasts, Keratinocytes, and Vascular Smooth Muscle Cells during Wound Healing - Jacob Smith; Vikrant Rai (Biomedicines, 2024)
Chronic diabetic foot ulcers (DFUs) are a significant complication of diabetes mellitus, often leading to amputation, increased morbidity, and a substantial financial burden. Even with the advancements in the treatment of DFU, the risk of amputation still exists, and this occurs due to the presence of gangrene and osteomyelitis. Nonhealing in a chronic DFU is due to decreased angiogenesis, granulation tissue formation, and extracellular matrix remodeling in the presence of persistent inflammation. During wound healing, the proliferation and migration of fibroblasts, smooth muscle cells, and keratinocytes play a critical role in extracellular matrix (ECM) remodeling, angiogenesis, and epithelialization. The molecular factors regulating the migration, proliferation, and differentiation of these cells are scarcely discussed in the literature. The literature review identifies the key factors influencing the proliferation, migration, and differentiation of fibroblasts, keratinocytes, and vascular smooth muscle cells (VSMCs), which are critical in wound healing. This is followed by a discussion on the various novel factors regulating the migration, proliferation, and differentiation of these cells but not in the context of wound healing; however, they may play a role. Using a network analysis, we examined the interactions between various factors, and the findings suggest that the novel factors identified may play a significant role in promoting angiogenesis, granulation tissue formation, and extracellular matrix remodeling during wound healing or DFU healing. However, these interactions warrant further investigation to establish their role alone or synergistically.